Editorial - Graham Connelly (Scottish Journal of Residential Child Care)
As I write this editorial in the midst of a global pandemic, it feels unreal to think how different the world was when I was writing the introduction to our February issue. All our lives have been changed utterly by COVID-19. While the virus itself appears generally to cause only mild symptoms in children, despite emerging evidence that some infected children can become seriously ill, the wider effects of COVID-19 on children and young people are likely to be tragically significant. The UN Children's Fund, UNICEF, has described the health crisis caused by COVID-19 as 'quickly becoming a child rights crisis' (UN, 2020). The problem is particularly acute in low and middle-income countries where financial and infrastructural pressures could have devastating effects on routine health provision, leading to vast numbers of deaths of young children in the absence of concerted efforts by the wealthiest countries. UNICEF also highlights potential impact on access to immunisations and the negative consequences of restrictions on normal living for mental health, education and child protection. Women and girls are likely to be particularly at increased risk of gender-based violence.